The Role of Creativity and Innovation in The Success of Small Businesses in East Nusa Tenggara - Minsel R. Munni; Eugenia S. Mine; Axel A. Patty; Petra L.M. Bria; Enike Tje Yustin Dima (International Journal of Information System and Innovation Management (IJISIM), 2026)
This study aims to analyze the role of creativity and innovation in the success of small businesses in East Nusa Tenggara. The method used in this research is a literature review with a qualitative descriptive approach, utilizing various scientific journals as data sources. The results show that creativity plays a role in generating new ideas that can be developed into business opportunities, while innovation plays a role in implementing these ideas into products or services that have economic value. Furthermore, creativity and innovation simultaneously exert a significant influence on business success. Therefore, business actors must continuously cultivate creativity and innovation to survive and compete in the modern era.